Bone formation effect of hydroxyapatite granules and platelet rich plasma in posterolateral lumbar spinal fusion - Zunariah Buyong (Kulliyyah of Medicine, International Islamic University Malaysia, 2011)
BACKGROUND: Hydroxyapatite is widely used as bone graft substitute. Platelet-rich plasma (PRP) is enriched with growth factors. Hypothetically combination of PRP and hydroxyapatite would augment bone formation effect of hydroxyapatite and widen its application in spinal fusion. OBJECTIVE: To compare new bone formation between hydroxyapatite granules alone; hydroxyapatite granules in combination with PRP; and autograft as the control. METHODOLOGY: First phase of the study dealt with the production of PRP and characterization of platelets by platelet counts and platelet morphology. Second phase involved spinal fusion surgery in twenty-four adult New Zealand white rabbits. All the animals underwent single level bilateral intertransverse process fusion at L5-L6 vertebrae. One side of the animals received either hydroxyapatite granules alone (HA group) or combination of hydroxyapatite granules and PRP (HAPRP group) while the contralateral side received autograft (Autograft group). Four animals each in HA vs. Autograft and HAPRP vs. Autograft were assessed either at 6, 12 or 16 weeks by plain radiograph, computed tomography scan, undecalcified histology, histomorphometry and scanning electron microscopy. Using the histomorphometric data, the mean percentage of new bone areas over the corresponding fusion masses was compared between groups. RESULTS: Mean platelet count in whole blood and PRP were 363 x 103/3uL (SD 112 x 103) and 1596 x 103/3uL (SD 512 x 103) respectively. Platelets showed minimal morphological changes. Autograft group showed significantly more new bone than HA and HAPRP at 6, 12 and 16 weeks (P=0.004, P<0.001 and P<0.001 respectively) but no significant difference between HA and HAPRP at 6, 12 and 16 weeks (P=0.154, P=0.929, P=0.487 respectively). Autograft, HA and HAPRP groups showed direct contact with new bone but Autograft demonstrated better integration than HA and HAPRP groups. CONCLUSION: Hydroxyapatite granules alone or in combination with PRP could not challenge autograft as bone graft substitute for posterolateral lumbar fusion. [305 words]